Effectiveness of SWOT and Kaizen in the Dominance of the Brain and the Hypocritical Personality of Physical Education Students - Raed Abdulameer Abbas Al-Mashhadi (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Teachers including university professors insist on keeping up to date with the updating of students' information and developing their scientific potentials, through use of diverse teaching strategies. Objectives. Identifying on the brain dominance and the hypocritical personality for students, knowledge effect SWOT and Kaizen strategy in the brain dominance and the hypocritical personality for student and knowledge the strategies which achieve more development in the brain dominance and reduce the hypocritical personality for students. Methods. Two methods were used the descriptive method in measurement of the brain dominance and hypocritical personality, and the experimental method to determine the effectiveness of using the SWOT and Kaizen strategies in developing the brain dominance and reduce the hypocritical personality with fourth stage students in Faculty of Physical Education and Sports Sciences, sample of the research 60 students and duration of the procedures 14 weeks. Results. The SWOT and Kaizen are of the important strategies. Teachers should use it with their students to learn and develop brain dominance and reduction hypocritical personality for students. Conclusion. Brain dominance and hypocritical personality is centered within the moderate normative level of the students, SWOT and Kaizen strategies play a small role in development of the brain dominance and effective in reducing the hypocritical personality for students, there is no difference between the Kaizen and SWOT strategies in developing the brain dominance and a SWOT strategy is better than Kaizen's strategy for reducing students' hypocritical personality.